Effects of Personality on Impulsive Buying Behavior: Evidence from a Developing Country - Dania Shakaib Farid; Mazhar Ali (Marketing and Branding Research, 2018)
Normally impulse buying is considered to take place in the presence of extrinsic factors which lure customers into unplanned buying. Th e role of intrinsic factors in generating impulse buying remains under-researched, espe cially in the context of a developing country like Pakistan. This study aims to study the impact of personality on impulse buying behavior. The effect of personality on impulse buying is measured through five personality traits, namely Op enness, Conscientiousness, Extr aversion, Agreeableness and Neuroticism-also known as the OCEAN Model. It is an explanatory research study involving 400 people of diverse backgrounds an d wide age brackets. Results indicated significant effects of Openness, Extraver sion, Conscientiousness and Neuroticism and insignificant effect of Agreeableness on Impulse Buying Behavior. This study has valuable implications for Pract itioners as well as Academics.
Keywords: 650; Impulsive Buying; Personality; Big Five; Openness; Conscientiousness; Extraversion; Agreeableness; Neuroticism; Pakistan